Microalgal oil production by green microalgae under heterotrophic cultivation - Leesing, Ratanaporn; Nontaso, Ngarmnit (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this research was to produce bio-oil from green microalgae under heterotrophic cultivation for used as feedstock for biodiesel production. The optimum conditions for lipid accumulation by the locally freshwater microalgaeisolateKKU-S2wereobtainedasfollows:NaNO3 as nitrogen source at 0.5 gL-1 and glucose as a carbon source at 50 gL-1withC/Nratioat280.Undertheoptimizedconditions,abiomassof6.3gL-1 ,specificgrowthrateat0.229d -1 and lipid contentof47.8%onacellulardry weightcouldbeachievedafterculturefor8days. Gaschromatographyanalysis revealed that lipidsoroils from theisolate KKU-S2contained mainlylong-chainfattyacids with16and18carbonatoms.Similar to vegetableoils, thelipidmainlycontainspalmiticacid,stearicacid,oleicacidandlinoleicacidandtheunsaturatedfattyacids and saturated fatty acid amount to about 36.1% and 63.9% of total fatty acid, respectively. Based on these compositional data, microalgaloils from thefreshwater microalgaeisolate KKU-S2areapotential feedstockforbiodieselproduction.